2011
DOI: 10.1161/circulationaha.110.015024
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Complications Related to Biventricular Defibrillator Implantation

Abstract: on behalf of the Cardiovascular Centers Participating in the ClinicalService ProjectBackground-Long-term data on device-related untoward events in patients receiving defibrillators for resynchronization therapy (CRT-D) are lacking. We quantified the frequency of repeat invasive procedures and the nature of long-term complications in current clinical practice and examined possible predictors of device-related events and their association with long-term patient outcome. Methods and Results-We analyzed data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…Some patients do not respond to the therapy, and other potential problems include phrenic stimulation, the absence of an adequate capture threshold, lead dislocations (especially the left ventricular [LV]), and in general, a higher rate of events related to the device compared with patients who receive cardiac defibrillator (ICD) implants without CRT [1][2][3]. To overcome many of these difficulties, new technical advances had been developed in the last few years but despite these developments, the leads cannot be properly positioned in some patients [4], and non-percutaneous surgical implantation is used whenever possible.…”
Section: Introductionmentioning
confidence: 99%
“…Some patients do not respond to the therapy, and other potential problems include phrenic stimulation, the absence of an adequate capture threshold, lead dislocations (especially the left ventricular [LV]), and in general, a higher rate of events related to the device compared with patients who receive cardiac defibrillator (ICD) implants without CRT [1][2][3]. To overcome many of these difficulties, new technical advances had been developed in the last few years but despite these developments, the leads cannot be properly positioned in some patients [4], and non-percutaneous surgical implantation is used whenever possible.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 3253 patients from 117 Italian centres who underwent de novo implantation of a CRT-D device, investigators found that device related events were more frequent in patients who received CRT-D devices compared with those who received ICDs only (single or dual chamber), although these events were not associated with a worse clinical outcome (123). In a multicentre, longitudinal cohort study of 104 049 patients receiving single and dual chamber ICDs, dual chamber device implantation was more common, but was associated with increased peri-procedural complications and inhospital mortality compared with single chamber ICDs (124).…”
Section: Implantable Cardioverter Defibrillatorsmentioning
confidence: 99%
“…71 Lastly, CRT is complex and implantation is associated with a greater risk of adverse events. 10 Furthermore, CRT device longevity is much less than an ICD meaning that patients may be exposed to long-term risk associated with device replacement. 72 The following summaries concern multiple topics pertinent to CRT therapy including evaluation of the cause of disparities in the uptake of CRT, 73 long-term untoward effects of CRT, 10 the benefit of CRT in patients with diabetic cardiomyopathy, 74 and the role of CRT in patients with HF and a narrow QRS (< 120ms).…”
Section: Cardiac Resynchronization Therapymentioning
confidence: 99%
“…8,9 Third, these devices are not without significant untoward effects; understanding and minimizing these adverse events, and in particular long-term events, is important particularly in the context of improving patient survival. 10 For example, patient longevity now often exceeds that of ICD's and 70% of patients are expected to require an ICD replacement in their lifetime exposing patients to risks from multiple surgical procedures. 11 Similarly, VADs are increasingly used as long-term destination therapy.…”
mentioning
confidence: 99%